There will be blood [videorecording (DVD)] - Anderson, Paul Thomas; Day-Lewis, Daniel; O'Connor, Kevin J., 1964-; Hinds, Ciarán, 1953-; Sinclair, Upton, 1878-1968 (Paramount Home Entertainment, 2008)
A down-and-out silver miner raising a son, self-made oilman Daniel Plainview, whose voracious appetite for oil turns him into a California tycoon in the early years of the 20th century. Getting the oil from the ground is an intensely physical process that later broadens into Plainview's equally indomitable urge to control land and power. Along the way, Plainview deals with a mighty derrick fire, a visit from a long-lost brother, and the ongoing involvement of Plainview's poker-faced adoptive son. Plainview's rivalry with Eli Sunday, the local preacher.